2019
DOI: 10.1088/1402-4896/ab1036
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement preservation in a system of two dipole–dipole interacting two-level atoms coupled with single mode cavity

Abstract: We address the problem of atom-atom entanglement dynamics control in a system of two different two-level atoms with dipole-dipole interaction coupled to a common single mode cavity with different coupling strengths. The control of entanglement dynamics is based on the parity kick method, and we use the antisymmetry properties of the Hamiltonian of the system to maintain atom-atom entanglement. We classify the possible controllable cases of this system. The control procedure is carried out with a sequence of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Inserting Eqs. (29)(30)(31)(32) into Eq. ( 17), we can get the density operator of the total system, i.e.…”
Section: Density Matrix Of Two V-type Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inserting Eqs. (29)(30)(31)(32) into Eq. ( 17), we can get the density operator of the total system, i.e.…”
Section: Density Matrix Of Two V-type Atomsmentioning
confidence: 99%
“…In the past decades, many effectively regulating methods have been proposed in order to protect quantum entanglement of open systems. For example, the detuning of cavity field or environment [25,26], the feedback and memory effects of non-Markovian environment [27][28][29], the dipole-dipole interaction between atoms [30,31], the external classical driving [26,32], the auxiliary qubits * Electronic address: zhmzc1997@hunnu.edu.cn [33], the quantum Zeno effect [34], the quantum weak measurement and reversal can all effectively protect entanglement of qubits from decoherence [35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Besides these, the dipole-dipole interaction between atoms can also protect the entanglement from sudden death. [45,46] In recent years, open qutrit systems are also concerned and the methods of protecting entanglement in open qubit systems have also been used to the qutrit systems because the latter is superior physical resources than the former in quantum information processing. For instance, the auxiliary quantum qutrits, [47] the Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42–44 ] Besides these, the dipole–dipole interaction between atoms can also protect the entanglement from sudden death. [ 45,46 ]…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the Zeno effect is a sufficient resource for the implementation of quantum logic gates 20,21 , which could be used as the basis of a quantum computer 21 or quantum repeaters 22 . The Zeno effect can also be used to prepare various nonclassical or entangled states [23][24][25][26][27] and to protect entanglement once it has been generated 28,29 . The anti-Zeno effect, by which repeated measurements increase the rate of transitions, may be useful in quantum heat engines 30 .…”
Section: Introductionmentioning
confidence: 99%